0014 Developing The Manchester Burn Simulation Framework: An Overview Of Progress Towards A Toolkit For Multidisciplinary Training, Assessment And Service Improvement On The Burns Unit. (1st November 2014) - Bedford, James D; Edwards, Jacky; Khwaja, Nadeem
Abstract : Background: Burn services should be founded on education and quality improvement, fostering a culture of continued learning and reflection on working practices, but the incidence of major burns is declining, with a reduction in the experiential learning needed to ensure we are effective, safe clinicians. We have previously found that simulating major burns encourages development of clinical, procedural and non-technical skills in team environments. We are now developing a simulation framework for education, evaluation and service analysis, based around accepted best practices for simulation. Methodology: Training: Curriculum-referenced scenarios were designed by an interdisciplinary team, including initial management of major burns, airway complications etc. Low- and high-fidelity mannequins were used in a simulation suite and for in-situ simulation on the burns unit. Video recording with immediate debriefing enhanced the learning experience. Assessment: Formative and summative assessment are possible. Part-task trainers evaluate procedural skills (burn size and depth assessment). Team interactions are assessed in complex scenarios using custom, activity-tracking software. Service improvement: For patient safety, activities are scrutinised to identify latent threats. For clinical effectiveness, pathways were mapped and refined using evidence and best practice principles. For cost efficiency, activity tracking and consumable use may be analysed to identify cost savings. Anticipated outcomes and impact: Participant surveys were scored positively: the multidisciplinary nature encouraged team working and openness, providing a safe opportunity for learning and development. Immersive scenarios were realistic, challenging and useful for developing and maintaining skills. Simulation can be widely applied to burns, contributing to training the whole team and to improving our services for patient benefit. We hope to refine our simulation framework over the coming year, including developing a set of measurable outcome measures in domains of knowledge/skill retention, reliability (for assessment) and objective measures of impact of "service improvement" simulations. References: Motola I, et al . Simulation in healthcare education: a best evidence practical guide . AMEE Guide No. 82. Med Teach 2013;35(10):e1511–30 McGaghie WC, et al . A critical review of simulation-based medical education research: 2003–2009 . Medical Education 2010;44(1):50–63 Wilson J, et al . Timeline of Events During Simulated Scenarios . Poster, ASPiH 2011, Cardiff Cooper S, et al . Rating medical emergency teamwork performance: development of the TEAM . Resuscitation . 2010, Apr;81(4):446–52 Van Beuzekom M, et al . Patient Safety: Latent Risk Factors . Br J Anaesth 2010;105(1):52–59 Catchpole K, et al . Teamwork and Error in the Operating Room: Analysis of Skills and Roles . Ann Surg 2008;247(4):699–706